The science of paddling, Part 1 - Burke, S. (2008)
As an engineer I find paddling not only fun, but technically fascinating. Spending hours at a time on the ergometer banking hours for the General Clinton 70-miler has given me time to ponder why canoes do what they do (and to contemplate why I`m so slow, but that`s another story). This is the first of what could turn out to be a multi-part series on the science underlying paddling, where we consider topics of (hopefully) general interest in paddling physics, exercise physiology, and materials technology.